Studi Literatur Tentang Ketidakpatuhan Wajib Pajak Terhadap Kewajiban Pelaporan Dan Pembayaran PPh Pasal 21 - Izdihar, Edgar Daffa; Dyah Ratnawati (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study investigates the key causes of non compliance among tax payers in reporting and settling their Article 21 income tax liabilities. Within Indonesia’s self-assessment tax system, tax payer compliance plays a critical role in achieving national revenue targets. This research employs a qualitative descriptive method through a literature review of secondary data sources. The finding sindicate that comprehension of tax regulations, the efficiency and performance of the tax administration system, High-quality tax services play a significant role in shaping taxpayer compliance. Additionally, tax avoid anceandevasion practices exacerbaten on compliance issues, driven by regulatory weaknesses and limited law enforcement. The study also high lights theim portance of implementing principles of good governance such as legal certainty, utility, transparency, and quality public service as preventive strategies against tax avoidance. These finding saim to support the creation of responsive tax policies that promote greater tax payer awareness and adherence.